Hiring challenges facing employers in small and medium enterprises (SMES) in Egypt’s textiles sector - Abughattas, Reem (AUC Knowledge Fountain, 2016)
Understanding what the labor market needs from the perspectives of employers is crucial in solving the unemployment problem in Egypt. The purpose of this study is to voice the views of employers as they describe the challenges they face in hiring within the specific sector of the textile industry in Egypt. The study is based on semi-structured interviews with eight business owners and general managers running small and medium enterprises (SMEs) in the textile sector. Despite labor surplus in the country, employers speak of a serious labor shortage problem in this sector where labor is described as the number one challenge to business performance and growth. Factors identified in interviews include shortage of technical skills, low quality of learning among graduates of technical schools, employment termination due to marriage (among female workers) and the attractiveness of temporary work within the informal economy to some of these workers due to its higher pay. The study addresses issues pertaining to the culture regarding manual jobs and technical and vocational education as well as job quality and career path issues.